TO ASSESS THE ANTERIOR CHAMBER PARAMETERS USING PENTACAM IN PRIMARY ANGLE CLOSURE SUSPECTS FOLLOWING PERIPHERAL LASER IRIDOTOMY - NETAM, MONIKA; SINGH, RAJINDER; KAUR, SURINDER; THUKRAL, JATIN; KAUR, HARBIR; MEENA, SURMILA; KAUR, PAWANDEEP (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the present study was to study the changes in anterior chamber parameters before and after laser peripheral iridotomy (LPI) in primary angle closure suspects (PACS) using pentacam. Methods: This was a prospective, non-randomized, and interventional study which was conducted on 40 patients of PACS attending the Outpatient Department of Ophthalmology, Government Medical College, Patiala. Evaluation of the anterior segment of the eye was done by Pentacam (Oculus) using rotating Scheimpflug imaging technology, before and after LPI. Results: Following LPI, anterior chamber volume (ACV) increased from 90.13±9.82 mm3 to 105.8±11.5 mm3; anterior chamber angle (ACA) increased from 27.01±3.23 degree to 28.13±2.29 degree. Peripheral anterior chamber depth (PACD) at 4 mm increased significantly in superior, inferior, nasal, and temporal quadrant in all cases. Conclusion: LPI serves both prophylactic and therapeutic benefit in PACS by increasing the ACV, ACA, and PACD, and thus preventing glaucoma. Pentacam is a useful tool to assess the efficacy of LPI and can guide further course of treatment.